Assessment of somatosensory sensitivity and activity of the electroencephalogram using body surface electrical stimulation in virtual reality environments. Issue 11 (3rd November 2020) - Kasai, Ryosuke; Itoh, Nana; Kamijo, Fuminori; Kano, Takashi; Shimamine, Tetsuya; Ogino, Minoru; Hinata, Nae; Tanaka, Kohei; Shinohara, Kazuhiko; Mizuno‐Matsumoto, Yuko
Abstract: The aim of this study was to assess Virtual Reality (VR) based visual auditory stimulation can relieve pain. To achieve this, the impact that body surface electrical stimulation has on the body surface potentials and activity in the central nervous system in VR environments were extracted. Twenty‐two adults participated in this study. The body surface potentials and Electroencephalogram frequencies were measured under various conditions: non‐viewing, viewing neutral clips, viewing unpleasant clips, and viewing pleasant clips. The pain index was calculated from the body surface potentials. Participants were asked to complete subjective pain measurement scales. Results showed that the pain index and the relative subjective pain score decreased when presented with unpleasant and pleasant video clips. The incidence of alpha waves declined when presented with unpleasant clips, while the incidence of beta waves increased when presented with unpleasant and pleasant video clips. Inattentiveness to pain due to VR immersion and descending pain inhibition due to awareness of emotional stress after viewing VR clips were considered to have contributed to the decline in the pain index and in relative subjective pain score. This study suggests that it is possible to relieve pain by VR viewing related to unpleasant or pleasant.